An empirical study of moving horizon closed-loop demand response scheduling. (August 2020) - Kelley, Morgan T.; Baldick, Ross; Baldea, Michael
Abstract: The potential of electricity-intensive chemical plants to engage in demand response (DR) initiatives in support of power grid operations has been the subject of many conceptual studies. In this work, using an industrially-relevant model of an air separation unit, we undertake an extensive simulation study of moving horizon (MH) scheduling approaches, where we "close the scheduling loop" based on updated information regarding disturbances such as changes in electricity prices, ambient conditions and chemical product demand. Our study produces several unexpected findings regarding the non-periodic nature of rescheduling solutions, the impact of the accuracy of disturbance forecasts on the economics of DR scheduling, and the interplay of simultaneously dealing with fluctuations on both the supply side (i.e., electricity prices) and the product demand side of the plant. We posit that the latter fluctuations pose significant limitations to the potential of a chemical plant to engage in DR. Highlights: Problem formulations for moving-horizon closed-loop scheduling for demand response. We consider fluctuations in electricity prices, weather and product demand. Plant dynamics are modeled explicitly. Extensive case study on industrially-relevant air separation unit model